Perancangan Jalur Evakuasi Kebakaran PT. PCC dengan Metode Algoritma Dijkstra - Raditya Azis; Bekti Nugrahadi; Anita Oktaviana Trisna Devi; Yunita Primasanti (Pusat Riset dan Inovasi Nasional, 2024)
Fires can occur at any time, therefore a mechanism is needed to evacuate the building in the event of a disaster. Generally, public facilities provide instructions and evacuation routes for exiting the building. PT. PCC has its headquarters in Australia. As for PT. PCC also opened a new factory located in Gresik Regency, East Java. The new factory does not yet have adequate fire evacuation routes. Even though inside the building there are materials and equipment that are flammable. Based on this, this research aims to design fire evacuation routes in PT buildings. PCC Gresik. The type of research used in this research is quantitative research. The method that the author applies is the Djikstra Algorithm to determine the shortest proposed route. The design of the evacuation route has 2 gathering points, namely at the front and back. There are 22 evacuation route signs, 6 exit signs, 2 gathering point signs, 2 emergency telephone signs and 10 Light Fire Extinguisher (APAR) signs. Evacuation route signs, exit signs and Light Fire Extinguisher (APAR) signs are planned to be installed on the walls. Assembly point signs and emergency telephone signs are installed on poles.